2019
DOI: 10.1039/c8fo01974f
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology oriented study reveals inflammatory state-dependent dietary supplement hepatotoxicity responses in normal and diseased rats

Abstract: Rhubarb, a well-used herbal and dietary supplement, has been widely used as a laxative in many countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Under liver fibrosis (immune tolerance), AQs showed therapeutic effect. While in normal state (immune activated), liver is more sensitive to AQs damage, which is related to Kupffer cells (liver macrophages) [157]. This exposes a shortcoming in the current research, that is, the in vitro effects and mechanism studies are relatively isolated and cannot fully simulate the in vivo pathological state, which may lead to contradictory results between in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 97%
“…Under liver fibrosis (immune tolerance), AQs showed therapeutic effect. While in normal state (immune activated), liver is more sensitive to AQs damage, which is related to Kupffer cells (liver macrophages) [157]. This exposes a shortcoming in the current research, that is, the in vitro effects and mechanism studies are relatively isolated and cannot fully simulate the in vivo pathological state, which may lead to contradictory results between in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 97%
“…Rhein exerts pro-inflammatory actions by increasing the interleukin-1 beta (IL-1β) and high-mobility group box-1(HMGB1) release, while downstream pro-inflammatory cytokines will, in turn, promote upstream intracellular signaling cascades and result in positive feedback pro-inflammatory signaling pathways. This amplifying mechanism of inflammatory signal pathways will eventually lead to further liver injury [ 39 ]. In this study, MA regulates inflammatory response through IL-2 and downstream PI3K-Akt signaling pathway and MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Routine toxicological studies have shown that no substantial hepatotoxicity has been observed in either raw or processed products or in different extracts within the range of the maximum tolerated dose in animal experiments, suggesting that it is safe to use Polygoni Multiflori Radix for people under normal circumstances [21,22] .…”
Section: Adverse Reactions and Safety Evaluation Of Polygoni Multiflo...mentioning
confidence: 99%